PENGARUH PERKEMBANGAN MOTORIK HALUS TERHADAP KEMAMPUAN MENULIS ANAK KELAS 1 SDN 1 TUKMUDAL - Amiratul Fadliillah Al Mahmudah; Aulia Rizkiyana; Nazzwa Hadita Putri; Nurkholis (PT. Hasba Edukasi Mandiri, 2025)
The development of fine motor skills is an important aspect of early childhood education, particularly in relation to writing abilities. This research aims to analyze the influence of fine motor skill development on the writing abilities of first-grade students at SDN 1 TUKMUDAL. The focus of the study includes three main aspects: first, identifying the level of fine motor skill development among students; second, assessing students' writing abilities; and third, determining the correlation between fine motor skill development and writing abilities. The research method used is qualitative, with data collection through observation, writing tests, and interviews with first-grade teachers. The results indicate that students with better fine motor skills have more advanced writing abilities in terms of letter formation, neatness, and writing speed. These findings are expected to provide insights for teachers in developing appropriate teaching strategies to enhance the fine motor skill development and writing abilities of early-grade students.